2015
DOI: 10.1002/aenm.201500985
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Phosphide‐Based Materials for Electrocatalytic Hydrogen Evolution

Abstract: for HER when nanoscale MoS 2 is used, [ 1 ] albeit bulk MoS 2 is suggested to be inactive towards HER. [ 2 ] Thus most studies have focused on designing thin layered/nanostructured MoS 2 nanomaterials with most exposed edges for HER. To this end, amorphous MoS 2,[ 3 ] MoS x nanosheets [ 4 ] were found to outperform bulk MoS 2 signifi cantly; layer-dependent attributes, [ 5 ] the correlation with intrinsic low conductivity out-of-plane, and phasedetermined performance have also been studied. [ 6 ] These fi ndi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
409
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 765 publications
(432 citation statements)
references
References 100 publications
(150 reference statements)
5
409
0
2
Order By: Relevance
“…For example, cobalt, [11][12][13] nickel, 14 copper [15][16][17] bimetallic catalyst, 18 transition metal carbide nanocrystals M3C (M: Fe, Co, Ni) encapsulated with vertically aligned graphene nanoribbons, 19 nitrogen and sulfur co-doped nanoporous graphene, 20 molybdenum sulfide (MoS 2 ), phosphide, carbon and noble metal-free catalysts are reported for the HER process. [21][22][23][24] Currently, nanoporous gold films (NPGF) have attracted attention for their widespread application in catalysis and in the sensors field because of their higher surface area in comparison to bulk gold electrodes, allowing superior electron transfer rate between the electrode-electrolyte interface. 25,26 Such platforms have been mainly prepared by alloying/dealloying or template methods, where hazardous chemicals are mostly used.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cobalt, [11][12][13] nickel, 14 copper [15][16][17] bimetallic catalyst, 18 transition metal carbide nanocrystals M3C (M: Fe, Co, Ni) encapsulated with vertically aligned graphene nanoribbons, 19 nitrogen and sulfur co-doped nanoporous graphene, 20 molybdenum sulfide (MoS 2 ), phosphide, carbon and noble metal-free catalysts are reported for the HER process. [21][22][23][24] Currently, nanoporous gold films (NPGF) have attracted attention for their widespread application in catalysis and in the sensors field because of their higher surface area in comparison to bulk gold electrodes, allowing superior electron transfer rate between the electrode-electrolyte interface. 25,26 Such platforms have been mainly prepared by alloying/dealloying or template methods, where hazardous chemicals are mostly used.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its particular platelet-like structure, the as-synthesized Ru-doped Ni 2 P catalyst not only exhibits a remarkably enhanced electrocatalytic hydrogen evolution reaction (HER) performances with an onset potential of 35 mV, tafel slope of 34 mV dec -1 and long-term stability, but also possesses superior oxygen evolution reaction (OER) properties with an onset potential of 1.54 V and robust durability, exceeding the performance of an individual Ru or Ni 2 P component and comparable to that of commercial 20% Pt/C, IrO 2 catalysts. As confirmed by HRTEM, line-scan, elemental-mapping and electrochemical analysis, the superior electrocatalytic bifunctionality of Rudoped Ni 2 P nanostructure can be attributed to the combined influence of the following factors: (1) The good intrinsic electrocatalytic properties for the exposed abundant (001) planet of Ni 2 P [1][2][3][4] ; (2) The special platelet-like structure ensures larger specific surface area compared to simple flat or hollow nanosheets, along with more accessible active sites caused by defects, facilitating their electrocatalytic process; (3) The introduced metallic Ru enables faster electron transfer rate of semiconductor Ni 2 P and moderate hydrogen adsorption energy, and thus are responsible for their remarkable electrocatalytic bifunctionality [5], [6] . In summary, such platelet-like Ru-doped Ni 2 P nanostrufcture is expected to serve as a new kind of robust catalyst for HER and OER applications.…”
Section: Extended Abstractmentioning
confidence: 85%
“…At this level of analysis, the results are similar to those reported previously. 31 60 review articles examined overall Li-S research and suggested areas for investigation. The direction for research recommended by the most recent 34, covering all review articles published between 2014 and 2017, was synthesized in Figure 1 as 'recommended areas'.…”
Section: Current Statusmentioning
confidence: 99%